Compliance Test of X-Ray Beam Quality Using HVL Parameter on Digital Mammography - Muhammad Yunus; Asmiati Amir; Mirnawati Mirnawati; Fitriani Fitriani; Siti Fatimah (Akademi Teknologi Industri Dewantara Palopo, 2022)
The compliance test of X-ray beam quality using HVL parameter on digital mammography was determined at a hospital in Makassar in 2019-2021. This measurement uses a ruler, X-ray multimeter, and aluminum filter. The exposure process is carried out at certain kVp and mAs conditions after placing the detector on the examination table. The HVL test to determine the X-ray beam quality is carried out by placing the detector 4 cm from the edge of the chest wall on the patient's table in an upright position facing the tube. The resulting HVL values ​​are 0.37, 0.37, and 0.38. This study resulted in a p-value of 0.000 (p < 0.05). Statistically, there is a significant difference in HVL values ​​in 2019-2021. The resulting HVL value is by the tolerance limit recommended by the IAEA, which is 0.31 ≤ HVL ≤ 0.58. These values ​​indicate that mammography works well, and it is safe for the patient.